Analisis Dampak Restrukturisasi Utang Terhadap Kinerja Keuangan Pada PT Krakatau Steel Tbk Periode 2015-2024 - Susniati; Eni Puji Astuti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the impact of debt restructuring on the financial performance of PT Krakatau Steel Tbk for the period 2015-2024. The USD 2.2 billion debt restructuring conducted in 2019 represents one of the largest restructurings in Indonesian industrial history. Financial performance is measured using liquidity ratios (Current Ratio and Quick Ratio), solvency ratio (Debt to Equity Ratio), and profitability ratio (Operating Profit Margin). This study employs a quantitative non-experimental causal comparative method by comparing financial performance five years before (2015-2019) and five years after (2020-2024) restructuring. Secondary data was obtained from financial statements published on the Indonesia Stock Exchange. Data analysis techniques include the Shapiro-Wilk normality test followed by descriptive comparative analysis to evaluate the consistency and sustainability of financial performance changes. The results indicate that debt restructuring did not provide a consistent and sustainable impact on the company's financial performance, resulting in the rejection of all four hypotheses (H1, H2, H3, H4). The average Current Ratio (57.8%), Quick Ratio (34.6%), and Operating Profit Margin (-4.25%) all fell far below industry standards, while the Debt to Equity Ratio surged drastically from an average of 261,96% to 562,08% post-restructuring. Although improvements occurred in 2020, the positive impact was only temporary. During 2021-2024, all indicators deteriorated, indicating that restructuring only provided a short-term temporary solution without sustainably improving the company's financial fundamentals